Mary’s Green Brilliance: The Case of the Virgin of Copacabana - Siracusano, Gabriela Silvana (2014)
This article reveals the latest research results on the polychromed sculpture of the Virgin of Copacabana of Bolivia, created by Francisco Tito Yupanqui in 1582. By considering its materials as documents of the past, this study examines the trade of pigments used in its manufacture and the use of gold, together with the presence of a recently-identified green color linked to prehispanic cultural practices. Other similar images, such as the Virgin of the Rosary in Tunja, the Carabuco Cross, and Mexico?s Virgin of Guadalupe, are also examined.